Optimal Frequency Offset Selection for FDA-MIMO Beampattern Design in the Range-Angle Plane - Jia, Wenkai; Jakobsson, Andreas; Wang, Wen-Qin (IEEE signal processing letters, 2024)
This work investigates the design of beampatterns for frequency diverse arrays-multiple-input multiple-output (FDA-MIMO) in the range-angle plane, in order to improve the approximation of a desired beampattern. Recognizing that the energy radiated by the array cannot be locked at a fixed range and angle, the beampattern is designed for the equivalent beampattern at the receiving end, differing from the traditional emphasis on the transmit beampattern. The proposed scheme formulates the beampattern design as a minimization problem, where the cost function is defined as the squared error between the designed and the given beampatterns. The developed scheme is then implemented through an optimal selection of both the FDA frequency offsets and the receiver steering weights. To this end, an iterative algorithm with monotonic convergence is introduced to solve the resulting non-convex optimization problem involving a fourth-order polynomial objective function as well as multiple non-convex constraints. Numerical simulations verify the performance of the algorithm and show that the proposed scheme can efficiently concentrate the energy of the echo signal on the desired region in the range-angle plane.